Glucose, starch, and dextrin utilization in the small intestine of steers - K.K. Kreikmeier; D.L. Harmon; T.B. Avery; Robert T. Brandt Jr. (Kansas Agricultural Experiment Station Research Reports, 1987)
Holstein steers (775 lbs) were surgically fitted with abomasal and ileal cannulae, portal and mesenteric venous catheters, and an elevated carotid artery. These steers were used to study starch digestion in the small intestine. Glucose, corn starch, and corn dextrin were infused into the abomasum at various levels and ileal digesta samples were collected. Disappearance of carbohydrate (CHO) in the small intestine was determined using Cr:EDTA as an indigestible marker. Blood samples were collected from the portal vein and carotid artery during carbohydrate infusion. Blood flow was determined, and net glucose absorption across the small intestine was calculated. Glucose infusions resulted in higher arterial glucose concentrations and increased net glucose absorption than either starch or dextrin infusions. Increasing infusion rates above 20 g/h for both starch and dextrin resulted in no further increases in net glucose absorption. Even though the enzymatic processes for starch and dextrin hydrolysis became saturated at a low infusion rate, the amount of starch and dextrin disappearing in the small intestine increased with higher infusion rates. This was accompanied by an increased volatile fatty acid (VFA) concentration in the ileal fluid with starch and dextrin infusions, but not when glucose was infused. Data from these experiments support two concepts: (1) microbial fermentation is involved in small-intestinal starch appearance and (2) starch and dextrin hydrolysis in the small intestine of steers is more rate limiting than glucose absorptive capacity.; Dairy Day, 1987, Kansas State University, Manhattan, KS, 1987;
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-114-S; Report of progress (Kansas Agricultural Experiment Station); 527; Dairy; Glucose; Starch; Dextrin; Small intestine